1934
DOI: 10.1042/bj0281603
|View full text |Cite
|
Sign up to set email alerts
|

The application of the Kober test to the quantitative estimation of oestrone and oestriol in human pregnancy urine

Abstract: IT is well known that both oestrone and oestriol when warmed with concentrated sulphuric acid give a green-fluorescing orange-coloured solution, thus resembling sterols and the bile acids. The colours given by the latter compounds are discharged by dilution with water, but as Kober [1931] showed, the oestrin colour on dilution with water is changed to a clear red, the green fluorescence being retained. His evidence suggested that this test was highly specific for oestrin. Kober also showed that the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1937
1937
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Efforts to quantify steroid hormones using colorimetry-based methods have existed since the 1930s [13][14][15]. One of the first methods used to define and quantify hormonal activity was also a bioassay [16].…”
Section: Determination Of Neuroactive Steroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to quantify steroid hormones using colorimetry-based methods have existed since the 1930s [13][14][15]. One of the first methods used to define and quantify hormonal activity was also a bioassay [16].…”
Section: Determination Of Neuroactive Steroidsmentioning
confidence: 99%
“…Quantitative MS analyses are mainly based on the use of internal standards, which are compounds of either similar structure, analyte analogues, or stable isotope-labeled (SIL) standards bearing, for example, 13 C, 15 N, 17 O, or 2 H [69,70]. The use of SIL standards has become increasingly dominant in recent years.…”
Section: Internal Standardsmentioning
confidence: 99%
“…Oestriol fractions containing KC-4 were prepared from ether extracts of the acid-hydrolysed urine both by the usual benzene-water partition procedure and by the original procedure of Cohen & Marrian (1934) involving extraction of a 'strong phenolic' fraction by 0-1 N-NaOH from ether. The latter procedure, being more economical in solvents, was clearly preferable for large-scale use.…”
Section: I8olation Of Kc-4mentioning
confidence: 99%
“…Marrian [1933], and Cohen and Marrian [1934] observed that allowing urine of pregnancy to putrefy was a more effective method of liberating oestrogens than hydrolysis by acid for 1 hour at 100°C, and Patterson [1937] based a routine method of chemical diagnosis of pregnancy on liberation of oestriol by incubation of urine with Bact. coli.…”
Section: Conditions Of Hydrolysis Of Urine By Acid Under Varying Condmentioning
confidence: 99%